(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Psychological happiness makes up an essential part of a person’sability to lead a fulfilling life, together with the ability to form andmaintain relations, to study, work and to make day-to-day decisions abouteducational, service, housing or other choices. This paper mainly focuses onfactors influencing psychological health for women.